2018
DOI: 10.1007/s10029-018-1761-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of umbilical hernia repair in patients with cirrhosis

Abstract: Within the limitations of a small study cohort and therefore an underpowered study, elective surgical repair of umbilical hernias in patients with cirrhosis, including decompensated cirrhosis, may not be associated with a significant increase in mortality when compared to a control cohort. Whilst complications are higher in cirrhotic patients, there is no difference in the rate of hernia recurrence. Emergency repairs of umbilical hernias are associated with a high complication rate in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
2
17
1
2
Order By: Relevance
“…Hernia recurrence is also lowered by using prosthetic mesh. This might explain the low recurrence rate found in our study (2%), similar to the ones reported in others series (1,7 to 2.7%) [25,26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hernia recurrence is also lowered by using prosthetic mesh. This might explain the low recurrence rate found in our study (2%), similar to the ones reported in others series (1,7 to 2.7%) [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…Morbidity and mortality rates vary according to the degree of liver disease. In Hew et al series, they were or CTP A patients, 18.8% and 0% for CTP B and 66.7% and 4.2% for CTP C, respectively [25]. This data shows that although complications become more prevalent as liver disease advances, the outcomes are still satisfactory, and thus CTP score itself should not be a sole reason to preclude elective hernia repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who are candidates for LT in the near future should defer hernia repair until during or after transplantation (162). For patients in whom transplantation is not imminent (i.e., low MELD), elective herniorrhaphy may be offered in select patients, after careful consideration of its risks and benefits in comparison to nonoperative management, with a possible need for an emergent operation (163)(164)(165)(166). Clinically apparent ascites should be controlled prior to elective herniorrhaphy, for which laparoscopic approaches are preferred (167).…”
Section: Abdominal Herniasmentioning
confidence: 99%
“…(162) For patients in whom transplantation is not imminent (i.e., low MELD), elective herniorrhaphy may be offered in select patients after careful consideration of its risks and benefits in comparison with nonoperative management, with a possible need for an emergent operation. (163)(164)(165)(166) Clinically apparent ascites should be controlled before elective herniorrhaphy, for which laparoscopic approaches are preferred. (167) The use of prosthetic mesh may reduce the recurrence rate but may increase the risk of infections and other complications.…”
Section: Abdominal Herniasmentioning
confidence: 99%